2023
DOI: 10.3390/machines11070693
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Social Robots for Speech and Language Therapy: A Review and Analysis of Interactive Scenarios

Abstract: The use of innovative technology in the field of Speech and Language Therapy (SLT) has gained significant attention nowadays. Despite being a promising research area, Socially Assistive Robots (SARs) have not been thoroughly studied and used in SLT. This paper makes two main contributions: firstly, providing a comprehensive review of existing research on the use of SARs to enhance communication skills in children and adolescents. Secondly, organizing the information into tables that categorize the interactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…The outlined tasks for each professional ensure a comprehensive approach to the educational and developmental needs of individuals with ASD, especially for language related issues (Georgieva-Tsaneva et al, 2023 ). Through collaboration and clear role delineation, the team can maximize the potential of robot-assisted sessions integrated with advanced conversational AI.…”
Section: Proposed Interaction Scenarios With Pepper Robotmentioning
confidence: 99%
“…The outlined tasks for each professional ensure a comprehensive approach to the educational and developmental needs of individuals with ASD, especially for language related issues (Georgieva-Tsaneva et al, 2023 ). Through collaboration and clear role delineation, the team can maximize the potential of robot-assisted sessions integrated with advanced conversational AI.…”
Section: Proposed Interaction Scenarios With Pepper Robotmentioning
confidence: 99%
“…One of the challenges during the sessions was that the children, especially those with ASD, had difficulties initiating, maintaining joint attention, and interacting with their interlocutor (Andreeva et al, 2022). After employing NAO in speech therapy, the project team found out that there was a necessity to broaden the communication environment between children and robots, so this is a perspective for future work with NAO (Georgieva-Tsaneva et al, 2023).…”
Section: Looking Aheadmentioning
confidence: 99%
“…Based on a comprehensive review, done by the scientists from the Institute of Robotics and other academic organisations, it has been found that there is an increasing number of studies that have documented encouraging outcomes in the implementation of SARs in the context of speech and language therapy (Georgieva-Tsaneva et al, 2023). Both the kids and the parents have enjoyed playing games and doing activities with the robots, which has motivated them to continue the sessions with SARs' help.…”
Section: Looking Aheadmentioning
confidence: 99%